PENGARUH PROSES EVALUASI KINERJA TERHADAP PERSEPSI PROCEDURAL FAIRNESS: STUDI DI PERGURUAN TINGGI - Dian Wijayanti; Sendy Cahyadi (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This study aims to test the process of performance evaluation particularly the formality and participation may effect the procedural fairness. Research conducted in universities as educational institutions that prioritizes quality of education involving all work units. Survey method was apllied by distributing questionnaires to 70 educational staff. 55 questionnaires were returned and 47 questionnaires were qualified to be analyzed in this study. Regression analysis was applied withing the research to conduct hypothesis testing. The results exposes formalities of performance evaluation effects the perception of procedural fairness, yet participation does not effect the perception of procedural fairness. It may happen since respondents prefer to understand the right instrument in assessing performance in performance evaluation is more important than participation in evaluation. Being aware of the results from the research, the process of performance evaluation requires formalized practical implication in order to obtain fairness evaluation process for everyone in the organization.